Treprostinil inhibits proliferation and extracellular matrix deposition by fibroblasts through cAMP activation - Lambers, Christopher (Sci Rep, 2018)
Idiopathic pulmonary fibrosis (IPF) is characterized by peripheral lung fibrosis and increased interstitial extracellular matrix (ECM) deposition. In IPF, tumor growth factor (TGF)-β1 which is the major stimulus of ECM deposition, and platelet derived growth factor (PDGF)-BB is a potent stimulus of fibrosis. Thus, the effect of Treprostinil on TGF-ß1 and PDGF-induced fibroblast proliferation and ECM deposition was investigated. Human peripheral lung fibroblasts of seven IPF patients and five lung donors were stimulated by PDGF, or TGF-β1, or the combination. Cells were pre-incubated (30 min) with either Treprostinil, forskolin, di-deoxyadenosine (DDA), or vehicle. Treprostinil time dependently activated cAMP thereby preventing PDGF-BB induced proliferation and TGF-β1 secretion. Cell counts indicated proliferation; α-smooth muscle actin (α-SMA) indicted differentiation, and collagen type-1 or fibronectin deposition remodeling. Myo-fibroblast indicating α-SMA expression was significantly reduced and its formation was altered by Treprostinil. Collagen type-I and fibronectin deposition were also reduced by Treprostinil. The effect of Treprostinil on collagen type-I deposition was cAMP sensitive as it was counteracted by DDA, while the effect on fibronectin was not cAMP mediated. Treprostinil antagonized the pro-fibrotic effects of both PDGF-BB and TGF-β1 in primary human lung fibroblasts. The data presented propose a therapeutic relevant anti-fibrotic effect of Treprostinil in IPF.